Tora! Tora! Tora! - Balsam, Martin, 1919-1996.; Cotten, Joseph, 1905-1994.; Fleischer, Richard; Fukasaku, Kinji; Goldsmith, Jerry; Marshall, E. G., 1914-1998.; Masuda, Toshio, 1927-; Mihashi, Tatsuya, 1923-2004.; Prange, Gordon W. (Gordon William), 1910-1980.; Robards, Jason; Senda, Koreya, 1904-1994.; Tamura, Takahiro; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Una dramatización crónicas del bombardeo de Pearl Harbor, tanto del punto de vista japonés como del estadounidense.
Based on the books: "Tora! Tora! Tora!" by Gordon W. Prange, and "The broken seal" by Ladislas Farago.
DISPONIBLE
Originally produced as a motion picture in 1970.
Special features: Commentary by director Richard Fleischer & Japanese film historian Stuart Galbraith IV; Two historical documentaries; AMC backstory: "Tora! Tora! Tora!"; Behind-the-scenes still galleries; Ten Fox movietone news features; Original theatrical trailer.
Directors of photography, Charles F. Wheeler, Osami Furuya, Sinsaku Himeda, Masamichi Satoh ; editors, Inoue Chikaya, Pembroke J. Herring, James E. Newcom ; music, Jerry Goldsmith.
Martin Balsam, Joseph Cotten, E.G. Marshall, James Whitmore, Jason Robards, Soh Yamamura, Tatsuya Mihashi, Takahiro Tamura, Eijiro Tono, Koreya Senda.
Keywords: Ataque a Pearl Harbor (Hawai), 1941.; Cine histórico; Guerra mundial II, 1939-1945.; Películas cinematográficas; Películas de aventuras